Yvonne Duplessis, 1912–2017 - Evrard, Renaud (Journal of Scientific Exploration, 2017)
Born in Jauchand in 1912, Yvonne Tuchmann-Duplessis died the 21st of September, 2017, in Paris, at the incredible age of 105. She was a prominent figure in French metapsychics during the second half of the Twentieth Century. Her work was at the crossroads of surrealism, perception, and extra-perception. She began with a Licence of Letters at the Sorbonne, and then received a philosophy diploma on “The coloration of non visual sensations” (1938) that anticipated her future research. Then, at the University of Montpellier, she prepared a Ph.D. on the “surrealist literary movement” (1945) and published it, after which it became the standard popular book on this topic since 1950 (Duplessis 2003). With its 18 reprints and its translations into 10 different languages, this work led her to become a respected scholar on surrealism. By chance, following a suggestion at one of her home literary meetings, she went to the experimental meetings conducted by the chemist René Warcollier, every Saturday at the Institut Métapsychique International (IMI). In the mid-1950s, he was one of the most famous researchers on telepathy. At his side, Duplessis became both a participant and a qualified researcher in all areas of metapsychics. She tested PK through famous subjects like Uri Geller (Duplessis & Bardot 1973) and his French avatar, Jean-Pierre Girard, but also teenage “mini-Gellers” (Duplessis & Bailly 1978, 1979–1980), and foreign subjects (e.g., Duplessis & Larcher 1973). She also tested ESP in various conditions: with blind people (Duplessis 1966a, 1968, 1972), and with synesthetes (Duplessis 1966b, 1968), and with new sets of symbolic colored cards (Duplessis & Olivyer 1971–1972).